1985
DOI: 10.1111/j.1365-2125.1985.tb05117.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of venous and capillary blood sampling for the clinical determination of tobramycin serum concentrations.

Abstract: Tobramycin concentrations have been determined in serum from capillary, venous and arterial blood samples taken from 16 patients during and after surgery. In 73 paired samples the concentrations in capillary samples were not significantly different from those measured in venous samples. The small concentration differences were neither dependent upon sampling time nor core‐peripheral temperature differences. In 26 paired samples, concentrations in capillary samples were not significantly different from those de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Likewise, in the literature, finger‐stick‐based capillary and venous concentrations were reported to be similar after repeated dosing for a number of antipsychotics16 and for, for example, theophylline,17 cyclosporin,18 and tobramycin 19…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Likewise, in the literature, finger‐stick‐based capillary and venous concentrations were reported to be similar after repeated dosing for a number of antipsychotics16 and for, for example, theophylline,17 cyclosporin,18 and tobramycin 19…”
Section: Discussionmentioning
confidence: 74%
“…Likewise, in the literature, finger-stickbased capillary and venous concentrations were reported to be similar after repeated dosing for a number of antipsychotics 16 and for, for example, theophylline, 17 cyclosporin, 18 and tobramycin. 19 Finally, variability (in %difference) was evaluated. When comparing 2 results obtained with a bioanalytical assay exhibiting acceptable performance (eg, 10% to 15% precision), one could expect a relatively wide distribution of the %difference for the individual samples; the distribution of %differences in the present multiple-dose study overlapped with the distributions obtained through a trial simulation that assumed that the assays were subject to a precision (%CV) of 10% to 15% ( Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…Which method was used for the peripheral sample was not recorded. While Lewis, Taylor, Williams, and Lewis () concluded that capillary samples of tobramycin are equivalent to venipuncture even in the presence of a core–peripheral temperature gradient, they noted a minimal negative bias along the magnitude seen in this study. Thus, the use of capillary samples could help explain some of the variance.…”
Section: Discussionmentioning
confidence: 45%
“…21 Aminoglycoside concentrations determined from finger lancet punctures were thought to be similar to concentrations determined from venipunctures, except that finger lancet punctures minimized blood loss in patients compared with venipunctures. 22,23 However, methods used to assess this similarity were insufficient to establish agreement and did not address the drawbacks of finger lancet punctures.…”
Section: Discussionmentioning
confidence: 99%